Autoantibodies against PFDN2 are associated with an increased risk of type 2 diabetes: A case‐control study. Issue 8 (30th August 2017) - Chang, Douglas C.; Piaggi, Paolo; Hanson, Robert L.; Knowler, William C.; Bogardus, Clifton; Krakoff, Jonathan
Abstract: Background: The adaptive immune system is involved in type 2 diabetes mellitus (T2DM), indicating the presence of unidentified autoantibodies that might be useful biomarkers for emerging immunomodulatory therapy. A prior microarray study with a small number of participants suggested the association of novel autoantibodies with T2DM in Southwest American Indians. We therefore sought to determine whether antibodies against 14 target proteins are associated with T2DM in a large case‐control study. Methods: Participants were adults (age 20‐59 y) of Southwest American Indian heritage. Plasma antibodies against 14 possible target proteins were measured in 476 cases with T2DM of less than 5 years duration and compared with 424 controls with normal glucose regulation. Results: Higher levels of antibodies against prefoldin subunit 2 (PFDN2) were associated with T2DM ( P  = .0001; Bonferroni‐corrected threshold for multiple tests = 0.0036 [α = 0.05]). The association between anti‐PFDN2 antibodies and T2DM remained in multivariable logistic regression (odds ratio 1.27; 95% confidence interval, 1.09‐1.49; per one SD difference in anti‐PFDN2 antibody). The odds of T2DM were increased in the highest anti‐PFDN2 antibody quintile by 66% compared with the lowest quintile. Differences in anti‐PFDN2 antibodies were most prominent among cases with earlier onset of disease (ie, age 20‐39 y) compared with controls. Conclusions: Anti‐PFDN2 antibodies are associated with T2DM and might be a useful biomarker. These findings indicate that autoimmunity may play a role in T2DM in Southwest American Indians, especially among adults presenting with young onset of disease.